90 anos de Histórias: manifestação multimodal do Ethos na conformação do caráter Institucional da UFMG - Graciele Martins Lourenço (2022)
This research has as its principle to approach the conformation of the institutional character of UFMG when it celebrates its ninety years. Focusing on the discursive construction of the ethos of nine characters selected from the video series entitled “90 years of stories”, produced by the University, this research aims to promote a theoretical approach between Rhetoric, Critical Discourse Analysis and Social Semiotics in their multimodal approach that allows the investigation of a possible multimodal manifestation of ethos within the organizational discourse. We seek to verify if, and how, the ethé are projected by the characters both for themselves and for the University, and also if, and how, the University is projected in this visual discourse, with the purpose of understanding, from this, which image UFMG outlines for itself, as an organizing instance of meaning. Considering the visual dimension as an element of outstanding importance in the audiovisual support chosen for the delivery of the narratives, this research is dedicated to analyzing the rhetorical behavior of other semiotic modes in a detailed way, in addition to the verbal mode, searching for ethical elements also in the modes and resources. visuals, such as scenery and camera shots, for example. Considering also the use of narratives in the storytelling format, by a public university, since this resource is commonly used by institutions belonging to the private sphere, this research touches on the issue of the commodification of public higher education as a social phenomenon to be observed in the discursive construction of the Uuniversity. The research also focuses on a deeper understanding of storytelling narratives as a rhetorical genre, establishing them as a field for staging a possible multimodal institutional ethos. In order to do so, through an interdisciplinary approach, we use a theoretical framework resulting from an articulation between concepts of Rhetoric, more specifically on the notion of ethos postulated by the ancients, Aristotle, Cicero and Quintilian, and its reappropriations, by the moderns such as Perelman and Olbrechts. -Tyteca and Amossy, with the concepts present in the studies on Social Semiotics and Multimodality regarding the Grammar of Visual Design by Kress and Van Leeuwen and the reflections on film productions with Bordwell; Thompson; Smith, and others, with regard to moving images. We also make use of Fairclough's three-dimensional model of discourse, in the search for understanding the construction of the social identity of a public higher education institution, through the stories told by the characters of the series "90 years of stories". Starting from a qualitative and interpretative analysis, we found ways to reflect on the rhetorical-multimodal dimension of discourse, also considering its relevance as a social, discursive and textual practice. In our results, we confirm our hypotheses of multimodal ethical projection, both on the part of the characters, who project themselves and the university with the help of the verbal and behavioral modes, and on the part of UFMG itself, which projects itself more evidently through camera mode making use of what we call visual modalization. This is composed of modalizing movements of approximation and removal that mark the institution's affinity and commitment to the utterances of the characters. In this way, the camera builds a separate visual narrative, anchored in specific ethical points that converge to legitimize the desired institutional ethos on completing 90 years. Finally, we understand that this interdisciplinary theoretical web that the thesis covered showed an infinite field of analytical possibilities, which presupposes the continuity of these studies. The rhetorical-multimodal dimension is evidenced in this research and expands the resources for analysis of the process of formation of meaning and discourse, with mobilizing and persuasive potential, revealing discursive dimensions that carry out different works in the field of orality, capable of bringing up meanings until then unobserved.